2008
DOI: 10.4103/0970-0358.41117
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar nerve palsy after open carpal tunnel decompression: Case report and review of the literature

Abstract: Open carpal tunnel release is the commonest surgical treatment of median nerve compression at the wrist. Although successful in most cases, there are well described complications. We report a case of laceration of the deep motor branch of the ulnar nerve at the level of the hook of hamate following a complicated carpal tunnel decompression. Good surgical technique and knowledge of wrist anatomy are essential for performing this apparently simple procedure safely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…8 Yoong et al reported a case of laceration of the DBUN following a carpal tunnel decompression. 9 DBUN injury also has been reported in association with HH excision. 10 Accurate understanding of the anatomical course of the DBUN may help to avoid these injuries.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…8 Yoong et al reported a case of laceration of the DBUN following a carpal tunnel decompression. 9 DBUN injury also has been reported in association with HH excision. 10 Accurate understanding of the anatomical course of the DBUN may help to avoid these injuries.…”
Section: Introductionmentioning
confidence: 79%
“…The usefulness of HRUS in detecting the DBUN and scanning its course has been confirmed in recent studies . Some studies analyzed surgical approaches and its complications in open carpal tunnel release and percutaneous pinning for carpal metacarpal fracture dislocations to prevent iatrogenic DBUN injury . The sonoanatomy of the nerve provides more detailed information that may limit nerve damage during various hand procedures.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The variability of clinical symptoms due to the presence of these communicating branches may lead to misdiagnosis or iatrogenic injuries (Ferrari and Gilbert, 1991;Bas and Kleinert, 1999;Loukas et al, 2007;Pellerin et al, 2010). Some studies of carpal tunnel release surgery have shown deficits in sensation of the third and fourth digits following surgery, or have described ''aberrant" branches of the median nerve (May and Rosen, 1981;Engineer et al, 2008;Yoong et al, 2008;Arrotegui, 2009;Demircay et al, 2009;Kaleff et al, 2010). Carpal tunnel release surgery usually involves an incision in the proximal palm near this communicating branch (Loukas et al, 2007;Arrotegui, 2009;Kaleff et al, 2010), and the resultant loss of sensation may be due to injury of these branches.…”
Section: Introductionmentioning
confidence: 99%